Odpowiedzi

Najlepsza Odpowiedź!
2010-02-22T21:55:54+01:00
A) 2x² - 10x -3x² + 6x +x² - 2x = -6x
b) a²+ab+ac -ab+b²- bc -ac + cb +c²= a²+b²+c²
c) x³ +2x² +x +2x³ -4x² +3= 3x³ -2x²+x +3
2010-02-22T21:55:56+01:00
A) 2x(x-5) -3(x² -2x) +(x-2)x=
2x²-10x-3x²+6x+x²-2x=-6x

b) a(a+b+c) -b(a-b+c) -c (a-b-c)=
a²+ab+ac-ab+b²-bc-ac+bc+c²=
a²+b²+c²

c) x(x²+2x+1) - (-4x³ +8x² -6) :2=
x³+2x²+x+2x³-4x²+3=
3x³-2x²+x+3
2010-02-22T21:58:25+01:00
A) 2x(x-5) -3(x² -2x) +(x-2)x
b) a(a+b+c) -b(a-b+c) -c (a-b-c)
c) x(x²+2x+1) - (-4x³ +8x² -6) :2

a)
= 2x²-10x-3x²+6x+x²-2x=2x²-3x²+x²-10x+6x-2x= -6x

b)
=a²+ab+ac-ab+b²-bc-ac+bc+c²=a²+b²+c²